Smartphone Screen Time and Physical Activity in a Sample of Czech and Slovak Secondary School Male Students - Štefan Adamčák; Michal Marko; Karol Görner (Jan Długosz University in Częstochowa, 2023)
Excessive use of smartphones can cause a decrease in physical activity. The present study aims at analysing and comparing the relationship between smartphone screen time and physical activity in a sample of Czech and Slovak secondary school male students. The survey instrument (nonstandardised) for measuring smartphone screen time and physical activity was intentional sampling of 1225 Czech and Slovak secondary school male students (aged 17.50 ± .65 years) who attended the last year of secondary schools. Chi-square test (χ2) and descriptive statistics were used to analyse and compare the data. Determining the relationship between smartphone screen time and physical activity was carried out for 9 months. After analysing the data, it turned out that 42.12% (n = 516) of the survey group pointed to 1 to 3 hours/ day of smartphone screen time (p ˂ 0.01). When evaluating their smartphone screen time, the survey group (n = 1225) considered it as adequate (58.21%, n = 713) (p ˂ 0.01). In terms of the smartphone screen time activity, the survey group (n = 1225) preferred social networking services (53.58%, n = 656) (p ˂ 0.01). Smartphone apps are adequate tools not only to improve quality of life, but also to promote leisure- time physical activity among adolescent boys.